2001
DOI: 10.1074/jbc.m104923200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Regulates the Phosphorylation and Cellular Localization of Occludin

Abstract: Occludin is an integral membrane phosphoprotein specifically associated with tight junctions, contributing to the structure and function of this intercellular seal. Occludin function is thought to be regulated by phosphorylation, but no information is available on the molecular pathways involved. In the present study, the involvement of the protein kinase C pathway in the regulation of the phosphorylation and cellular distribution of occludin has been investigated. Phorbol 12-myristate 13-acetate and 1,2-dioct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
155
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 34 publications
7
155
1
2
Order By: Relevance
“…After washing three times with PBS, 0.5% Triton X-100, bound proteins were eluted with Laemmli buffer (eluate). Eluate and unbound fractions were analyzed by SDS-PAGE and Western blot as described previously (26).…”
Section: Measurements Of Transepithelial Electrical Resistance (Teer)mentioning
confidence: 99%
“…After washing three times with PBS, 0.5% Triton X-100, bound proteins were eluted with Laemmli buffer (eluate). Eluate and unbound fractions were analyzed by SDS-PAGE and Western blot as described previously (26).…”
Section: Measurements Of Transepithelial Electrical Resistance (Teer)mentioning
confidence: 99%
“…In non-epithelial cells ZO-1 is a major component of AJ, whereas in epithelial cells it is localized at TJ by directly binding to claudins (6). Occludin, one of the transmembrane proteins of TJ, is a multiphosphoprotein involved in regulation of TJ (7). It has four transmembrane domains with two extracellular loops and a cytosolic N and C terminus.…”
mentioning
confidence: 99%
“…More recently, nitric oxide (NO) and Ca 2ϩ have been shown to partially mediate the effects of H and H/R on cellular permeability, though the mechanisms by which NO and Ca 2ϩ may cause these permeability changes are still unclear (17, 35). However, it has recently been suggested that phosphorylation of the TJ proteins can affect the functionality of the TJ (4,23,33,46). Several intracellular signaling molecules have been shown to regulate TJ protein phosphorylation, including tyrosine kinases, MAPK, and PKC (4,33).…”
mentioning
confidence: 99%
“…However, it has recently been suggested that phosphorylation of the TJ proteins can affect the functionality of the TJ (4,23,33,46). Several intracellular signaling molecules have been shown to regulate TJ protein phosphorylation, including tyrosine kinases, MAPK, and PKC (4,33).…”
mentioning
confidence: 99%